Experiments on the Release of CMOS-Micromachined Metal Layers. (18th April 2010) - Fernández, Daniel; Ricart, Jordi; Madrenas, Jordi
Abstract : We present experimental results on the release of MEMS devices manufactured using the standard CMOS interconnection metal layers as structural elements and the insulating silicon dioxide as sacrificial layers. Experiments compare the release results of four different etching agents in a CMOS technology (hydrofluoric acid, ammonium fluoride, a mixture of acetic acid and ammonium fluoride, and hydrogen fluoride), describe various phenomena found during the etching process, and show the release results of multilayer structures.